GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP PEMANDU WISATA DALAM PENANGANAN GIGITAN KERA DI MONKEY FOREST UBUD - Ni Luh Dian Mirayanti; Putu Ayu Asri Damayanti; Ni Luh Putu Eva Yanti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
Tourist visited to Ubud Monkey Forest have been very high for the past 3 years. Monkeys can bite and scratch when they feel threatened so the role of a tour guide who visits tourists to the Ubud Monkey Forest is very important in handling early monkey bite cases to prevent possible dangerous or life-threatening infections. This research is a kind of quantitative research with descriptive method. This study uses a cross sectional approach with a sample of 62 respondents obtained by purposive sampling technique. The results of the study regarding the characteristics of respondents were (6.5%) aged 17-25 years, (33.6%) aged (26-35 years), (33.6%) aged (36-45 years), (20.7 %) aged 46-55 years, and (4.8%) aged 56-65 years. Male gender (100%), education in junior high school (8.1%), high school (54.8%), Diploma (25.8%), undergraduate strata (11.3%). A total of (74.25%) received information from others, and (25.8%) from mass media. (6.5%) respondents had experience in handling monkey bites and (93.5%) never. The level of knowledge of respondents in handling monkey bites was good knowledge (19.3%), sufficient (56.5%), and lack of knowledge (24.2%). Descriptions of the attitude of respondents in handling monkey bites were (21%) having a good attitude, (7.8% enough), and (11.2%) lacking. This research is expected to become new data in supporting nursing education, especially in the field of tourism nursing, to become data and evaluation materials for tour guides, health offices and tourism managers.